2022
DOI: 10.1590/2175-8239-jbn-2021-0115
|View full text |Cite
|
Sign up to set email alerts
|

Glycosuria in primary glomerulopathies: prevalence and prognostic significance

Abstract: Introduction: Tubular damage is common in glomerular diseases (GD). Glycosuria is a marker of tubular dysfunction and may be used to detect tubular lesion and CKD progression. The aim of this study was to evaluate the prevalence and prognostic value of glycosuria at the time of diagnosis in primary glomerulopathies (PG). Methods: We conducted a 24-month retrospective study in patients diagnosed with PG in our center between 2009 and 2020. We excluded diabetic patients, use of SGLT2 inhibitors, transplant pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“… 26 Nevertheless, glycosuria in patients with glomerular disease was significantly related to pronounced tubular atrophy and interstitial fibrosis with a poorer prognosis. 27 , 28 Using the samples obtained from patients with kidney disease, urinary glucose was also found to have a significant role in representing deteriorated kidney function even after adjusting for diabetes status.…”
Section: Discussionmentioning
confidence: 99%
“… 26 Nevertheless, glycosuria in patients with glomerular disease was significantly related to pronounced tubular atrophy and interstitial fibrosis with a poorer prognosis. 27 , 28 Using the samples obtained from patients with kidney disease, urinary glucose was also found to have a significant role in representing deteriorated kidney function even after adjusting for diabetes status.…”
Section: Discussionmentioning
confidence: 99%
“…In the early stage of DN, renal tubular lesions appear independently of glomerular lesions and affect the glomerulus through various pathophysiological mechanisms. Injury of renal tubular epithelial cells plays a central role in renal tubular diseases [13] . High glucose induces secretion of proin ammatory and brogenic factors in renal tubular epithelial cells through various signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these patients progressed to ESRD rapidly. Some previous researches showed that the prevalence of MN combined with glycosuria at the time of diagnose was as high as 17.9% which was higher than that of the global CKD [ 13 , 14 ]. And patients with positive urine glucose had higher serum creatinine (Scr), more urine protein, lower serum albumin, more severe interstitial fibrosis, and tubular atrophy.…”
Section: Introductionmentioning
confidence: 99%
“…And patients with positive urine glucose had higher serum creatinine (Scr), more urine protein, lower serum albumin, more severe interstitial fibrosis, and tubular atrophy. Also, the prevalence of ESRD and 50% increase in basal Scr was higher in patients with glycosuria [ 14 ]. However, there was no study about the occurrence of urine glucose during the long-term follow-up in iMN so far.…”
Section: Introductionmentioning
confidence: 99%